EVALUATION OF THE GOVERNMENT AGENCY PERFORMANCE ACCOUNTABILITY SYSTEM (SAKIP) IN NORTH MINAHASA REGENCY - Cintia Oktavia Nafai; Jetty E. H. Mokat; Steven V. Tarore (Journal of International Islamic Law, Human Right and Public Policy, 2026)
The purpose of this study is to evaluate the implementation of the Government Agency Performance Accountability System (SAKIP) in the Organizational Section of the Regional Secretariat of North Minahasa Regency, analyze the causes of its suboptimality, and identify supporting and inhibiting factors in the implementation of SAKIP. The research method used is a qualitative approach with a descriptive research type. Data collection was carried out through in-depth interviews, observation, and documentation. Data analysis refers to the Miles, Huberman, and Saldana model, including data collection, data condensation, data presentation, and conclusion drawing. Data validity was tested using source and technique triangulation. The results of the study indicate that the implementation of SAKIP is not optimal. This is due to several problems, namely: 1) Performance Planning, there is a lack of synchronization between strategic and annual planning documents and the less than optimal alignment of Key Performance Indicators with the RPJMD, 2) Performance Measurement still faces problems in the validity of achievement data, differences in OPD understanding in distinguishing output and outcome indicators, and limitations of the performance information system 3) Performance Reporting is hampered by delays in submitting LKjIP, non-uniformity in understanding reporting standards, and low quality of performance achievement analysis 4) Internal Evaluation and Follow-up show that OPD understanding of evaluation results is still low, follow-up is not consistent between OPDs, and coordination has not been effective. The supporting factors for SAKIP implementation include the commitment of regional leaders and regulatory support. The main inhibiting factors are limited human resource capacity, weak coordination between regional devices, and the less than optimal use of information technology.